Use of chat bots in the educational process of a higher education institution - Nalyvaiko, O.; Maliutina, A. (Scientific notes of the pedagogical department, 2021)
The article presents the results of theoretical and practical scientific research on the feasibility of using chatbots in the educational process. The main purpose of the study was to determine the importance of chatbots in the educational process of students of higher education institutions and to consider their current involvement and prospects in the educational process of HEIs. Achieving this purpose involves a number of tasks: to provide analysis of previous studies on the use of chatbots in various fields; to find out students' awareness of chatbots and their functionality; provide information about the capabilities of chatbots for the learning process; identify prospects for the development of this tool for participants in the educational process. The authors consider the theoretical provisions of the introduction of chatbot technology in the educational process of HEIs. The practical part of the study consisted of personal data obtained during the survey, which was conducted using Google services (Google Forms). 69 respondents (mostly senior students) from HEIs in the Kharkiv region took part in the survey. The questionnaire consists of 10 open and closed questions. Based on the obtained results and previous research, the authors proposed ways to use chatbots in the educational process of HEIs and highlighted the positive aspects of using chatbots in the educational process. Prospects for the development of learning through chatbots depend on the individual capabilities of students. Because the experience of working with modern technology among students is in most cases at a high level, so we see the involvement of chatbots as a simple and fast process that does not require large funds and resources.